ANALISIS PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Nasabah Bank BCA di Kota Semarang) - Maharani, Nandita Ratu; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT BCA is one of the largest banks in Indonesia. However, in 2020, Bank BCA received many complaints through their Halo BCA service. When compared to its competitors, Bank BCA has the fewest number of customers but the most complaints throughout the years 2019-2021. These complaints prove that customers are not satisfied with the services provided by Bank BCA. In this study, inconsistencies were found with previous research, that service quality has a significant impact on customer loyalty and that service quality has no significant impact on customer loyalty. The purpose of this study is to analyze the quality of service and customer trust in relation to customer loyalty, with customer satisfaction as the intervening variable among Bank BCA customers in the city of Semarang. The population in this study is the community of Semarang who have been Bank BCA customers for the last three months and have used Bank BCA services in Semarang. The sample used consisted of 125 respondents who were selected using purposive sampling technique. The data obtained were then analyzed using the Structural Equation Model (SEM) method using Smart Partial Least Square (Smart PLS) 3.0 as the analysis tool. The results of this study show that service quality and trust have a positive and significant relationship with customer satisfaction and customer loyalty. Likewise, customer satisfaction also has a positive and significant relationship with customer loyalty. The biggest influence is shown by the trust variable in customer satisfaction, which is 0.473